Synthesis and Biological Studies of Some Isoxazolines - R. MOHANE, SONALI; THAKARE, V.G.; BERAD, B.N. (Asian Journal of Chemistry, 2010)
3-[3-(2-Hydroxyphenyl)-4,5-dihydro-isoxazol-5-yl]chromen-4-one (IVa-d) have been synthesized from appropriate α,β-unsaturated ketones (IIIa-d) and hydroxylamine hydrochloride in presence of ethanol as a moistening solvent under microwave irradiation. The compounds have been characterized by elemental analysis and spectral data. The antimicrobial activities of the compounds have also been evaluated.